Green consumption behaviour in Indonesia: exploring the role of government support - Achmad Iqbal; Erwin Saraswati; Sutrisno T; Muhammad Tojibussabirin (Cogent Social Sciences, 2024)
The issue of waste, particularly food waste, in Indonesia remains unresolved. This study examined the impact of attitude (AT), subjective norms (SN), perceived behavioral control (PBC), environmental knowledge (EK), social media influence (SMI), and government support (GS) on green consumption behavior (GCB) in Indonesia, utilizing the Theory of Planned Behavior (TPB) as a theoretical framework. Using a quantitative methodology, primary data were collected through surveys of 448 participants, including Generation Z and non-Generation Z individuals, using volunteer sampling. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that SN, PBC, EK, SMI, and GS positively influence GCB in Indonesian society, while AT has no significant impact. Furthermore, GS moderated the relationship between the SMI and GCB. These findings provide valuable insights for policymakers and businesses to design strategies to enhance green consumption behavior in Indonesia by focusing on the roles of social media and government support. This study contributes to the understanding of the factors driving GCB in Indonesia, highlighting the importance of environmental knowledge, social influence, and governmental initiatives in promoting sustainable consumption practices, especially among the younger generations.